Erratum to: Finding new physics without learning about it: anomaly detection as a tool for searches at colliders (The European Physical Journal C, (2021), 81, 1, (27), 10.1140/epjc/s10052-020-08807-w) - Romão, M. C. (2021)
Erratum to: Finding new physics without learning about it: anomaly detection as a tool for searches at colliders (The European Physical Journal C, (2021), 81, 1, (27), 10.1140/epjc/s10052-020-08807-w)